A mineralogically-inspired silver–bismuth hybrid material: an efficient heterogeneous catalyst for the direct synthesis of nitriles from terminal alkynes. Issue 5 (19th January 2018) - Ötvös, Sándor B.; Mészáros, Rebeka; Varga, Gábor; Kocsis, Marianna; Kónya, Zoltán; Kukovecz, Ákos; Pusztai, Péter; Sipos, Pál; Pálinkó, István; Fülöp, Ferenc
Abstract : A silver-containing hybrid material is reported as an effective heterogeneous catalyst for the direct synthesis of organic nitriles from terminal alkynes. Abstract : The synthesis and characterization of a silver-containing hybrid material is reported as a novel heterogeneous noble metal catalyst. In order to eliminate the need for traditional immobilization techniques, and to create a solid material with structurally-bound silver catalytic centers, the layered structure of a naturally occurring mineral served as the basis of the initial catalyst design. The novel material was prepared by means of the urea-mediated homogeneous precipitation of the corresponding metal nitrates, and was fully characterized by means of diverse instrumental techniques (X-ray diffractometry, Raman, IR, UV-Vis, EPR, X-ray photoelectron spectroscopies, thermal methods as well as atomic force, scanning and transmission electron microscopies). The as-prepared material exhibited outstanding activity in silver-catalyzed CC bond activation to yield organic nitriles directly from terminal alkynes with less environmental concerns as compared to the classical synthesis methods. The effects of the reaction time, the temperature, as well as the role of various solvents, nitrogen sources and additives were carefully scrutinized in order to achieve high-yielding and selective nitrile formation. The heterogeneous nature of the reaction was verified and the solid catalyst was recycled and reused numerous times without loss of its activity or degradation of its structure, thereby offering a sustainable synthetic methodology.